1992
DOI: 10.2105/ajph.82.6.867
|View full text |Cite
|
Sign up to set email alerts
|

First-year impact of the 1989 California cigarette tax increase on cigarette consumption.

Abstract: IntrdutionWith the passage of the voter-initiated California Proposition 99, the state excise tax on cigarettes was increased by 25 cents per package, effective January 1, 1989.1 Although the initiative earmarked a percentage of the new revenues for tobacco use control, medical care, and tobacco-related research,2 excise taxes have also been recognized as having potential public health benefits by reducing cigarette consumption.3-7 The purpose of this study was to estimate the impact of the 1989 tax increase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
2
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 4 publications
0
23
2
1
Order By: Relevance
“…Of the adults who were smoking prior to implementation of the tax, 3.5% indicated that they had stopped smoking, owing in some degree to the price increase. This is an impressive finding, particularly in light of the fact that shortly after the tax increase, tobacco companies lowered the price of major brands and more low-cost generic cigarettes appeared on the market.…”
Section: Discussionmentioning
confidence: 99%
“…Of the adults who were smoking prior to implementation of the tax, 3.5% indicated that they had stopped smoking, owing in some degree to the price increase. This is an impressive finding, particularly in light of the fact that shortly after the tax increase, tobacco companies lowered the price of major brands and more low-cost generic cigarettes appeared on the market.…”
Section: Discussionmentioning
confidence: 99%
“…Los resultados sostienen, principalmente, que los precios y el consumo tienen una relación inversa, es decir que cuando los primeros se incrementan, el consumo disminuye. [13][14][15][16][17][18] La edad ha sido considerada como un elemento importante, particularmente dentro de los modelos económicos de la adicción, en donde se menciona que el consumo actual de los fumadores adultos está condicionado por el consumo en la adolescencia. 19 Esto se refleja en una estimación de la ENA de 1998, en donde se calcula que el promedio de cajetillas consumidas al año, en una población adolescente de entre 12 y 14 años, fue de 26.7 mientras que en una población de 55 a 65 años el consumo promedio fue 133.8 cajetillas.…”
Section: Introductionunclassified
“…One possible explanation for the different rates of decrease in recent smoking prevalence for California and the remainder of the nation is the continued presence of California's tobacco control program (Proposition 99). Proposition 99 was associated with an acceleration in the rate of decline of per capita cigarette consumption in California 7,29,[33][34][35][36][37][38][39][40][41][42][43][44][45] and produced a 10% to 13% longterm reduction in cigarette consumption. 44 Both short-term effects of the cigarette tax increase and long-term effects due to the tax increase or other programs funded by Proposition 99 have been demonstrated, 38,42 and evidence exists that the antismoking media campaign specifically resulted in reduced cigarette consumption.…”
Section: Discussionmentioning
confidence: 99%